Instagram Digital Storytelling in Teaching English Literature: Students’ Interpretation, Classroom Engagement, and Pedagogical Challenges - Agustine Clara Mamentu; Fridolin Joseph Philip Kukus; Yapi Henri Wongkar; Firjinia Putri Utami Sukirman; Sabrina Wardatul Jannah Husain; Samuel Frederick Lasut (GLENS: Global English Insights Journal, 2026)
Instagram Digital Storytelling is a teaching method in which students use or create, compose, and share narratives using various features; this is not just uploading photos, but a pedagogical process. This study examines students' and lecturers' interpretations of the use of Instagram digital storytelling in English literature learning. The data were collected through semi-structured interviews with three lecturers and fifteen students, as well as documentation in the form of Instagram content, learning notes, and student interpretive assignments. The results showed that students interpreted digital storytelling on Instagram as a multimodal literary text that combines captions, images, colors, videos, sounds, symbols, expressions, and personal experiences. Student interpretations focused not only on plot and messages but also encompassed moral, social, and humanistic values ​​such as empathy, responsibility, respect for differences, and concern for human emotional experiences. Furthermore, Instagram increased student engagement emotionally, cognitively, and behaviorally through discussions, comments, content creation, assignment uploads, and literary reflections. However, the use of Instagram also faces challenges such as shallow content, the dominance of visual aspects, potential distractions, misinterpretations, technical limitations, and the need for lecturer guidance. Therefore, Instagram is most effectively used as a complementary medium before students are directed to more in-depth literary analysis.